PENGARUH MODEL OPEN ENDED DENGAN DUKUNGAN QUIZIZZ TERHADAP PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA - Damar Lini; Samijo; Bambang Agus Sulistyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Open Ended learning model assisted by Quizizz media on the motivation and learning outcomes of mathematics of grade VII junior high school students. The background of this study is the low motivation and learning outcomes of students due to conventional learning that does not involve students actively. The Open Ended model encourages students to think critically and creatively through questions with various possible answers, while Quizizz as an interactive quiz-based learning media creates a fun and competitive learning atmosphere. This study uses a quantitative approach with a one group pretest-posttest design and involves 13 grade VII students of SMP Muhammadiyah 4 Prambon. The instruments used are learning motivation questionnaires and pretest-posttest essay tests to measure learning outcomes. Data analysis is carried out descriptively and inferentially. The results of the study showed an increase in student motivation and learning outcomes after the implementation of the Open Ended model assisted by Quizizz. Thus, the combination of this model and media is effective in increasing enthusiasm, active participation, and understanding of students' mathematical concepts. This study recommends the use of this approach as an innovative strategy in junior high school mathematics learning.